Effect of Different Growing Systems of Apple on Trunk and Branch Diseases and Pests - Maria BOROVINOVA; Vilina PETROVA; Svetla MANEVA (Notulae Botanicae Horti Agrobotanici Cluj-Napoca, 2012)
The presented study aimed to determine apples trunk and branch diseases and pests in three growing systems conventional, integrated and biological (organic). The investigations were made on an experimental apple orchard (1 ha) of the Institute of Agriculture at Kyustendil, Southwest Bulgaria in four consecutive years from 2007 to 2010. Three scab resistant cultivars Prima, Florina and Erwin Baur grafted on rootstocks MM106 were planted in 1996. The orchard was divided into four plots. One plot was treated conventionally with a normal pesticide programme, two plots were treated integrated according to the general principles, rules and standards of integrated apple production and one plot for biological (organic). The monitoring of pests and diseases and assessment of their density were done every two weeks. It was established that during the experimental period important disease and pests on apple trees in different growing systems were black rot Botryosphaeria obtusa, apple clearwig moth Synanthedon myopaeformis and shorthole borer Scolytus rugulosus. The damages by trunk and branch diseases and pests on apple were considerable higher in biological growing system. The mean rate of attack of cultivar Erwin Baur by Botryosphaeria obtusa in biological and conventional growing systems was 52.35% and 4.65%, respectively. The percentage of damaged by Scolytus rugulosus trunk and branch area per tree reach to 58.74 in biological and 0.23 in conventional system. Reduced vitality of apple trees growing with out pesticides and mineral fertilizers in biological growing system was the reason for strong infection of Botryosphaeria obtusa and attack of Synanthedon myopaeformis and Scolytus rugulosus.